Comparative Study of Experimental Testing and Finite Element Simulation of Hexagonal Crash Boxes Made from AA 6061-T4 - Ahmad Yunus Nasution; Dodi Peradile; Togu Martua Siregar; Riki Effendi; Gunawan Hidayat (Faculty of Engineering, Universitas Muhammadiyah Jakarta, 2025)
This study evaluates the crashworthiness of hexagonal AA 6061-T4 crash boxes with perforations by integrating experimental compression tests and finite element (FEM) simulations. The research aims to analyze the influence of perforation patterns (one, two, and three holes) on energy absorption and deformation behavior. Simulation results using ABAQUS CAE 6.14 show strong agreement with experimental data, with discrepancies of less than 5% in peak force and energy absorption. The validated model confirms the effectiveness of perforated hexagonal designs in improving energy absorption while reducing peak reaction forces. These findings provide validated design insights for optimizing lightweight crash boxes and enhancing passive safety systems in automotive engineering.